PECULIARITIES OF PRODUCTION AND CLASSIFICATION OF CASTINGS BY TECHNOLOGICAL COMPLEXITY OF PRODUCTION - A. P. Melnikov; M. A. Sadoha (Литьë и металлургия, 2007)
The peculiarity of production and classification of alloys by technological complexity of production are given.